ASSESSMENT OF THE LEVEL OF EXCRETION OF MARKERS OF ANGIOGENESIS IN PATIENTS WITH RENAL NEPHROSCLEROSIS DUE TO CHRONIC PYELONEPHRITIS - Shukurova Umida Polatovna (Scholars Digest Publishing, 2024)
Currently, based on the results of a large number of population and scientific studies conducted worldwide, special attention is paid to the development of optimal treatment regimens depending on the presence of clinical components of renal nephrosclerosis in chronic pyelonephritis. At the same time, identifying tubulointerstitial fibrosis in the formation of chronic kidney disease in a pathogenetic interrelationship with inflammatory processes is one of the urgent tasks of optimizing differential therapy. The article fully covers the determination of the prognostic value of markers for predicting the degree of damage to kidney structures during the treatment stages of patients with nephrosclerosis on the basis of chronic pyelonephritis.
Keywords: chronic pyelonephritis, kidney nephrosclerosis, angiogenesis regulators, kidney microcirculation network, antiangiogenic factor, endothelial cells.